2000
DOI: 10.1038/sj.bmt.1702661
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors influencing the development of chronic graft-versus-host disease in a murine model

Abstract: Summary:Graft-versus-host disease (GVHD) is a major complication of bone marrow transplantation that can occur in either acute or chronic forms. Much of the long-term pathology seen in chronic GVHD is a result of autoantibody production. In the DBA/2 → B6D2F1 murine model of chronic GVHD, anti-ssDNA autoantibodies can be detected by 14 days post cell transfer. These autoantibodies are not observed in B6D2F1 recipients of cells from C57BL/6 or B10.D2 donors, which develop acute rather than chronic GVHD. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Several parent 3 F1 transplantation models, while described as cGVHD models, result in a disease more similar to systemic lupus erythematosus than cGVHD. [33][34][35][36] 49 Although this model is best viewed as a de novo model of cGVHD, its value lies in the strong resemblance to the clinicopathologic features found in both primary and secondary cGVHD in humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several parent 3 F1 transplantation models, while described as cGVHD models, result in a disease more similar to systemic lupus erythematosus than cGVHD. [33][34][35][36] 49 Although this model is best viewed as a de novo model of cGVHD, its value lies in the strong resemblance to the clinicopathologic features found in both primary and secondary cGVHD in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Several parent 3 F1 transplantation models, while described as cGVHD models, result in a disease more similar to systemic lupus erythematosus than cGVHD. [33][34][35][36] However, the B10.D2 (H-2 d ) 3 BALB/c (H-2 d ) MHC-compatible, multiple minor histocompatibility antigen (miHA)-incompatible model of cGVHD [37][38][39][40][41] does share critical characteristics with human cGVHD. Its dominant features include skin fibrosis (due to increased collagen deposition) as well as lichenoid subepithelial infiltrates, follicular drop-out, loss of subdermal fat, and dermal mononuclear infiltrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of lymphocytes of Bm12 mice into C57BL/6 mice leads to cGVHD and a SLE-like disease [19,20]. These human SLE-like animals were mainly characterized by immune complex-mediated glomerulonephritis.…”
Section: Discussionmentioning
confidence: 98%
“…Some non-MHC loci that modify alloresponse were shown to be minor antigens coded in the mouse by Mtv [13]. Several groups have reported that recognition of a host vSAG (viral superantigens) (Mls1a and Mls2a) by donor T cells may determine the manifestations of GVHD in several parental/F1 strain combinations [14,15], others indicate roles of non-MHC non-Mls genes in MLR [16,17] and in GVHD [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%